Essays on fiscal and macroprudential policy - Jang, Hun (2024)
Since the Global Financial Crisis of 2008-09, pursuing appropriate policy measures to achieve macroeconomic stability has been a primary concern for academia and policymakers. Given this focus, this thesis presents three studies conducted to analyze the effects of fiscal and macroprudential policies and offer pertinent policy implications. Chapter 2, “How should fiscal policies be used as a macroprudential tool?”, conducts a theoretical investigation into the impact of property taxes and mortgage deductions on house prices and household indebtedness, which are key macroeconomic aggregates in macroprudential policy operations. The study pays particular attention to how tax revenues are used and examines the side effects of combined tax and spending policies on economic output and household welfare, shedding light on how fiscal policies should be utilized as macroprudential tools. The results indicate that while such tax measures help curb increases in house prices and credit levels, they tend to have adverse effects on output in the short term due to a decrease in residential investment. Furthermore, these fiscal measures carry significant equity implications, particularly undermining the welfare of borrowers. The adequate allocation of tax revenues is crucial to mitigate such negative consequences. Public investment spending, to the extent that public and private capital are complementary, can expedite recovery by fostering the accumulation of private capital and thus minimize harm to the welfare of borrowers. Chapter 3, “Debt Finance Bias and Macroprudential Policy,” discusses how proper macroprudential policy operations can address distortions arising from tax design that could potentially damage macroeconomic stability. Previous studies have indicated that corporate income tax (CIT) systems that allow interest payments to be deductible but not for dividends contain a bias towards debt, inducing firms to have excessive leverage and making them vulnerable to shocks. Using a dynamic stochastic general equilibrium model with a banking sector and corporate finance structure that entails both debt and equity financing, the study first shows that without time-varying capital requirements, an economy with higher corporate income tax rates and greater debt deductibility is characterized by a more substantial debt finance bias, leading to larger financial and macroeconomic volatility. It then demonstrates that volatility can be reduced by imposing a countercyclical capital buffer, whereby the bank’s capital-to-debt ratio is significantly more responsive to deviations of the credit-to-GDP ratio from the steady state. Finally, Chapter 4 (co-authored with Dr. Atsuyoshi Morozumi), “Liquidity Constraints and the Consumption Effects of Recurrent Property Taxes,” empirically examines the impact of recurrent property taxes on consumer spending. We identify unexpected changes in these taxes by exploiting a unique feature of the South Korean property tax system. Specifically, while the governments annually reassess residential properties to update the recurrent tax base, their assessment methods are unknown to homeowners, such that each year’s recurrent tax liability inevitably contains an unexpected component for homeowners. We then show that an unexpected increase in recurrent taxes generally has an insignificant consumption effect. However, it reduces liquidity-constrained homeowners’ spending in particular, which happens primarily through a fall in their spending on durable goods. The results thus offer support for utilizing recurrent taxes as a means of raising revenue, provided that arrangements are made for liquidity-constrained homeowners to alleviate the unequal consumption effects.